Kif4 Is Essential for Mouse Oocyte Meiosis. - Nicole J Camlin (PLoS ONE, 2017)
Progression through the meiotic cell cycle must be strictly regulated in oocytes to generate viable embryos and offspring. During mitosis, the kinesin motor protein Kif4 is indispensable for chromosome condensation and separation, midzone formation and cytokinesis. Additionally, the bioactivity of Kif4 is dependent on phosphorylation via Aurora Kinase B and Cdk1, which regulate Kif4 function throughout mitosis. Here, we examine the role of Kif4 in mammalian oocyte meiosis. Kif4 localized in the cytoplasm throughout meiosis I and II, but was also observed to have a dynamic subcellular distribution, associating with both microtubules and kinetochores at different stages of development. Co-localization and proximity ligation assays revealed that the kinetochore proteins, CENP-C and Ndc80, are potential Kif4 interacting proteins. Functional analysis of Kif4 in oocytes via antisense knock-down demonstrated that this protein was not essential for meiosis I completion. However, Kif4 depleted oocytes displayed enlarged polar bodies and abnormal metaphase II spindles, indicating an essential role for this protein for correct asymmetric cell division in meiosis I. Further investigation of the phosphoregulation of meiotic Kif4 revealed that Aurora Kinase and Cdk activity is critical for Kif4 kinetochore localization and interaction with Ndc80 and CENP-C. Finally, Kif4 protein but not gene expression was found to be upregulated with age, suggesting a role for this protein in the decline of oocyte quality with age.